Success Rate of Inseminations Dependent on Maternal Age? An Analysis of 4246 Insemination Cycles - Schorsch, M.; Gomez, R.; Hahn, T.; Hoelscher-Obermaier, J.; Seufert, R.; Skala, C. (Geburtshilfe und Frauenheilkunde, 2013)
Intrauterine insemination (IUI) has latterly become less important in reproductive medicine. The aim of this retrospective analysis was to identify and evaluate the success rates of repeated insemination cycles in women of different ages. All women who underwent intrauterine insemination in the Wiesbaden Fertility Clinic between 1998 and 2010 were included in the analysis. Additional inclusion criteria were: not more than 45 years old, previous FSH stimulation and slight to moderate subfertility of the male partner. A total of 4246 insemination cycles in 1612 patients were included in the analysis. The average number of IUI cycles per patient was 2.24 (1–14). Patient age ranged from 19 to 45 years (mean: 33.9 years). Logistic regression analysis showed a drop in pregnancy rates with increasing age (p = 0.000). However, for the first three cycles the pregnancy rates for women aged 40 and 41 did not differ from those of women aged between 35 and 39 years. Overall pregnancy rates were stable in women up to the age of 40, even after several insemination cycles (7.5 and 10 %). Insemination is therefore still an effective procedure in selected patients. Stable pregnancy rates were recorded even after more than 3 cycles. After 3 cycles, the success rates for women aged 40 and 41 did not differ from those of women below the age of 40.
Keywords: insemination; infertility; reproductive medicine; pregnancy